2021
DOI: 10.1111/jdv.17469
|View full text |Cite
|
Sign up to set email alerts
|

Childhood epidermal necrolysis and erythema multiforme major: a multicentre French cohort study of 62 patients

Abstract: Introduction The distinction between epidermal necrolysis [EN; including Stevens–Johnson syndrome (SJS), toxic epidermal necrolysis (TEN) and overlap syndrome] and erythema multiforme major (EMM) in children is confusing. We aimed to better describe and compare these entities. Materials and methods This French retrospective multicentre study included children ≤18 years old referred for EN or EMM between 1 January 2008 and 1 March 2019. According to pictures, children were reclassified into TEN/overlap, SJS or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Toxicology testing on blood, urine, or hair to confirm drug exposure if the history is unclear [23].…”
Section: Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…Toxicology testing on blood, urine, or hair to confirm drug exposure if the history is unclear [23].…”
Section: Managementmentioning
confidence: 99%
“…An important element of follow-up for the patient and family who has survived DEN or RIME is patient and family education about the disease and its trigger or risk of recurrence. For RIME, the risk of recurrence is 8–42% [12,20 ▪ ,23,55 ▪ ]. A recent pediatric retrospective case series showed that counseling about recurrence tended to be poorer for patients with an infectious trigger, whose families should be informed that subsequent infections can provoke the same reaction [20 ▪ ].…”
Section: Follow-up Future Planning and Sequelaementioning
confidence: 99%
See 3 more Smart Citations